A Novel Highly Accurate Finite-Element Family. (5th September 2017) - Bernardini, Giovanni; Cetta, Fabio; Morino, Luigi
Abstract : A novelN th order finite element for interior acoustics and structural dynamics is presented, withN arbitrarily large. The element is based upon a three-dimensional extension of the Coons patch technique, which combines high-order Lagrange and Hermite interpolation schemes. Numerical applications are presented, which include the evaluation of the natural frequencies and modes of vibration of (1) air inside a cavity (interior acoustics) and (2) finite-thickness beams and plates (structural dynamics). The numerical results presented are assessed through a comparison with analytical and numerical results. They show that the proposed methodology is highly accurate. The main advantages however are (1) its flexibility in obtaining different level of accuracy (p -convergence) simply by increasing the number of nodes, as one would do forh -convergence, (2) the applicability to arbitrarily complex configurations, and (3) the ability to treat beam- and shell-like structures as three-dimensional small-thickness elements.